The effect of discussion supported geographical research trips on academic achievement - (:unkn) unknown (My University, 2011)
A geographical research trip was organised for the aim of determining the effects of discussion supported geographical research trips on students' academic achievements. A total of 44 geograhpy student teachers participated in this study which was done with a quasi-experimental model. A knowledge test about the tour region and its' close environment was applied to the participants before the trip. However, 19 questions were asked to the participants in this test and 4 of these questions were on individual data, while 15 of them examined students' academic knowledge. Geographical concepts (66.7%) which were determined through knowledge test were discussed during the trip, but 33.3% of them were not discussed. About 4 weeks after the trip, the same knowledge test was applied again. As such, quantitative data that were obtained through knowledge test were analysed with Kolmogorov-Smirnov test, dependent group t-test and Pearson product moment correlation coefficient, while the qualitative data were analysed with content analysis. Achievement level about the concepts in the knowledge test and, if available, complications and mistakes about concepts were determined. Results and suggestions were presented with connection to data and interpretations. © 2011 Academic Journals.
Keywords: Discussion supported trip; Geoghraphy education; Geographical research trip